Engaging People with Lived Experience in Co-design of Future Palliative Care Services. Issue 9 (4th July 2021) - French, Tara; Raman, Sneha
ABSTRACT: For people living with a life-limiting condition it is challenging to contribute to the design of future services due to limited research foregrounding meaningful engagement of 'vulnerable groups' in co-design. This paper shares findings and critical reflections on sensitively engaging people with lived experience of palliative care transitions, and making their lived experiences visible and legitimate in the co-design process. This paper presents an asset-based approach for reframing 'vulnerability', and visual and narrative tools to facilitate participation. Sharing critical reflections on the design tools and methods, the paper discusses future considerations for engaging 'invisible communities' in co-design of public services.